Increasing Overall Equipment Effectiveness in the Computer Numerical Control Lathe Machines using the Total Productive Maintenance Approach - Tri Ngudi Wiyatno; Hibarkah Kurnia (OPSI, 2022)
Production machines are the most important part of a production system. Machines need effective and efficient maintenance to be able to guarantee and support the production process to run well. The steel industry is an industry that produces various types and shapes of steel with one of the machines being Computer Numerical Control (CNC) type BT-A16. These machines often have problems such as downtime that interfere with the production experience. The purpose of this research is to find out the problems in the CNC BT-A16 production machine and provide recommendations for improvements to improve machine performance or Overall Equipment Effectiveness (OEE). The approach used is Total Productive Maintenance by calculating the OEE value. Problem analysis was carried out through Focus Group Discussion with expert judgment when determining the Failure Mode Effect Analysis (FMEA) analysis. Research findings indicate that the cause of the engine is not optimal comes from abnormal heat in the gearbox and machine spindle components caused by operator error when inputting data. The definite improvement is making a special schedule for maintenance, checking all maintenance schedules, and conducting training to increase knowledge and skills. The results of the corrective action show an increase in the OEE value from 70.8% to 79.9% or an increase of 9.1%, so the increase in the OEE value will increase the efficiency of the BT-A16 CNC lathe.